Clinical Features of Spinal Cord Hemangioblastoma in a Dog - Michaels, Jennifer; Thomas, William; Ferguson, Sylvia; Hecht, Silke (Frontiers in Veterinary Science, 2015)
A 2-year-old male, intact Yorkshire terrier presented with a one-month history of progressive paraparesis. Neurologic examination revealed paraplegia with absent deep pain perception, decreased right pelvic limb withdrawal reflex, and lumbar pain consistent with an L4-S2 neurolocalization. Magnetic resonance imaging showed a single, well-demarcated, intramedullary mass centered over the L3-4 disc space. A hemilaminectomy was performed, and the mass was removed en bloc. Histopathological evaluation was consistent with a hemangioblastoma. Follow-up magnetic resonance imaging nine months after surgery showed no evidence of tumor recurrence, and the dog was ambulatory paraparetic at that time. This case is consistent with a previous histopathologic report of spinal cord hemangioblastoma in a dog and provides additional clinical information regarding diagnosis, treatment, and outcome associated with this tumor type.